ROLE OF WITHANIA SOMNIFERA IN PREVENTION AND TREATMENT OF CANCER: AN OVERVIEW (International Journal of Pharmaceutical Sciences and Drug Research, 2011)
Cancer is hyperproliferative disorder that involves transformation, dysregulation of apoptosis, proliferation, invasion, angiogenesis and metastasis. Millions of people die every year with different types of cancer such as lung cancer and mesothelioma from inhaling asbestos fibers and tobacco smoke, or leukemia from exposure to benzene at their workplaces. In the last century, great advances were made in modern medical system in cure and prevent of this disease. However, success rates are very low. Withania somnifera (WS) has been used as traditional medicine for decades for the treatment of various ailments. The various parts of WS and its constituents are effective in prevention and treatment of different kinds of cancer like colon cancer, lung cancer, blood cancer, skin cancer, breast cancer, renal cancer, fibrosarcoma, prostate cancer, pancreatic cancer. We are conducting clinical studies to prove the efficacy of WS in prevention and treatment of different forms of cancer including prostate and lung cancers, especially in last stages, and this wonder medicinal herb is found to be beneficial in many patients. We have some cases of lung cancer that were refused modern therapy and recovered clinically and radiologically with our therapy of Ashwagandha. Clinical studies suggest its use as anti-tumor and immunomodulatory agent in sarcoma, brain cancer, uterine tumor, fibroids and other tumors including endodermal carcinoma. Therefore, this medicinal herb WS alone can be used as alternative medicine in the treatment of cancer patients or it can also be used as adjunct/ complimentary medicine along with chemotherapy or radiotherapy to patients. As the causative factors in formation and development of cancerous conditions can be multifactorial eg. stress- physical, chemical, biological and emotional, viral infection like Herpes cause several time more cancer of bladder, low immune syndrome plays major role in spread and causation of cancer, environmental chemical toxins, allopathic drugs, pesticide infected food with heavy metals and some not properly developed metallic preparation of Ayurvedic or other Folk Medicine can be a causative factor, leave aside genetic processes of the Individual for the development of the risk of cancer. If we look in the properties of WS like adaptogen/ anti-stress agent, immunomodulator, antioxidant (reducing free radical damage, anabolic effect, improving resistance of body, reducing fatigue and detoxificant effects, we are inclined to suggests that WS works through all above mechanisms in controlling the dreaded cancer, rather than its effect on stopping the cell division. As during radio and chemotherapy body’s natural normal cells are also killed and low immunity develops, WS helps prevent these adverse effects of both and helps patients better recovery and life styles. However, multicentric long term clinical studies by oncologists, although deviated from their routine, must be carried out on WS to prove our contentions.